Kajian Etnobotani Rempah sebagai Representasi Kearifan Lokal dan Pengetahuan Tradisional Masyarakat Desa Punten Kota Batu - Aulinisa Gita Herdiyanti; Aurelia Laudya Bella; Nurul Hudayah; Fahrul Ghani Muhaimin; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The use of spices by local communities represents an important aspect of local wisdom, reflecting the relationship between humans and biological resources. This study aims to identify the diversity of spices and analyze their utilization levels as a representation of traditional knowledge in Punten Village, Batu City. This research employed a mixed-methods approach with an exploratory sequential design integrating qualitative and quantitative methods. Qualitative data was obtained through interviews with informants determined using purposive sampling techniques followed by snowball sampling, then observations and documentation were collected as supporting data. Meanwhile, quantitative data were obtained through a questionnaire survey distributed to 95 respondents determined using the Slovin formula with a 10% margin of error. Data were analyzed descriptively for qualitative data and using ethnobotanical indices for quantitative data, including Informant Consensus Factor (ICF), Relative Frequency of Citation (RFC), Species Use Value (SUV), Family Use Value (FUV), Plant Part Use Value (PPUV), and Fidelity Level (FL), to assess the importance and utilization of spices. The results showed 14 spice species belonging to eight families, with Zingiberaceae as the dominant family. The highest ICF value was found in the culinary category (0.98), while the highest RFC (0.96) and SUV (1.68) values were observed in Zingiber officinale. The Zingiberaceae family had the highest FUV value (0.91), and rhizomes were the most utilized plant parts (42.7%). These findings highlight that spice utilization in Punten Village reflects strong traditional knowledge and demonstrates the potential for biodiversity conservation based on local wisdom.